Rancang Bangun Oven Pengering Buah Salak dengan Metode QFD (Quality Function Deployment) dan Pertimbangan Aspek Ergonomis Pengguna - Farahdiansari, Ardana Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Salak dates are one of the iconic snack from Bojonegoro city. The production process turns out a long time because the drying process takes 3 (three) days. Improvement of the drying process with tools is expected to be a solution to achieve production efficiency of Salak Dates. The design of this drying oven is a research in the field of simple technology design with the aim of achieving production efficiency. This research uses the QFD (Quality Function Deployment) method and the ergonomic aspects for the user. The QFD aspect is used to find out what the user wants in achieving the desired product according to user needs. While the Ergonomic aspect is used as a consideration size of the product to be made can be safe and comfortable while being used. The combination of these two methods is expected to make drying oven products effective and appropriate.